Direct preparation of a graphene oxide modified monolith in a glass syringe as a solid‐phase extraction cartridge for the extraction of quaternary ammonium alkaloids from Chinese patent medicine. Issue 22 (9th October 2017) - Liang, Xiaojing; Wang, Licheng; Wang, Shuai; Li, Yijing; Guo, Yong
Abstract: Packed cartridges have been widely used in solid‐phase extraction. However, there are still some drawbacks, such as they are blocked easily and the method is time‐consuming. In view of the advantages of monoliths, a monolithic extraction material has been directly synthesized in a glass syringe without any gap between the monolith and syringe inner wall. The monolithic syringe was modified with graphene oxide by loading graphene oxide dispersion onto it. The content of graphene oxide and the surface topography of the monolith have been evaluated by elemental analysis and scanning electron microscopy, respectively, which confirmed the successful modification. This prepared graphene oxide‐modified monolithic syringe was directly used as a traditional solid‐phase extraction cartridge. As expected, it shows good permeability and excellent capability for the extraction of quaternary ammonium alkaloids. The sample loading velocity (1–6 mL/min) does not affect the recovery. Under the optimal conditions, good linearities ( R  = 0.9992–0.9998) were obtained for five quaternary ammonium alkaloids, and the limits of detection and quantification were 0.5‐1 and 1–2 μg/L, respectively. The proposed method was successfully applied for the analysis of quaternary ammonium alkaloids in Chinese patent medicine.